Analisa Sistem Ordering Material Plastik pada PT XYZ dengan menggunakan Metode Kepner-Tregoe Problem Solving - Jonny Lin (Binus Business Review, 2015)
PT XYZ has faced a problem related to its plastik material ordering system in which its quantity purchase order calculation result was so different with its manual calculation that its material logictic staff was needed to make a proper correction. Therefore, this research was taken in order to help the staff to analyze its root cause so that the proper improvement could be taken and the quantity purchase order calculation will be equal to its manual calculation. By deploying Kepner-Tregoe problem solving, the staff found that the difference was due to miss-managed algorthim of the system because the quantity purchase order that is still open was not considered in the calculation and after proper improvement was taken, then the quantity purchase order calculation is equal to the manual calculation.